Quarantine Process Management – Case of Poland - Anna KACZOROWSKA; Jolanta SLONIEC (Communications of International Proceedings, 2021)
The COVID-19 pandemic and the related quarantine have become a great challenge for societies and governments. The aim of the article is to present, analyze and evaluate the management of the quarantine process in Poland. The applied research methods included a critical study of specialist literature and selected legal acts. A very important element of the research was a diagnostic survey conducted on a group of 407 respondents. The research and analyses have confirmed the lack of due diligence in managing the quarantine process. The results of the research prove that quarantine leads to deterioration of the economic situation and psychophysical form of the people undergoing it. The quarantine process is controlled through the “Household Quarantine” (HQ) application. The acceptance level for this application is higher if the respondents are aware of the data it collects. Acceptance for vaccinations is higher in older age groups and in those whose psychophysical condition deteriorated after the quarantine.